Lifelong Learning of Employees: Is Generative Artificial Intelligence Becoming the Most Important Source of Knowledge? - Klobasa, Nik; Žnidaršič, Jana (Celovita pot izobraževanja: Od ideje do mreženja, 2026)
The chapter addresses lifelong learning among employees in the context of the rapid development of artificial intelligence, comparing the role of formal, informal education and generative AI tools, when employees search for knowledge. The theoretical part highlights the importance of continuous knowledge upgrading, and shows the advantages of formal and informal education, which is largely supported by AI. The empirical part is based on qualitative research with employee interviews. The findings show that AI is used primarily for the rapid acquisition of explicit knowledge, but not tacit knowledge and knowledge based on years of experience and intuition. The research confirms that the role of mentors in the AI era is not decreasing, but rather transforming. The mentor is no longer the only source of knowledge, but becomes primarily a guide for critical assessment and interpretation of information. AI does not replace existing forms of learning, but changes the structure between formal, informal and self-regulated learning. The latter is becoming increasingly important. It continuously complements informal and formal education, which remains crucial for the systematic acquisition of key knowledge and new competencies, career advancement and the acquisition of officially recognized qualifications.